If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 + -6x = 3x + -9 Reorder the terms: -5 + 5x + -6x = 3x + -9 Combine like terms: 5x + -6x = -1x -5 + -1x = 3x + -9 Reorder the terms: -5 + -1x = -9 + 3x Solving -5 + -1x = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + -1x + -3x = -9 + 3x + -3x Combine like terms: -1x + -3x = -4x -5 + -4x = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -4x = -9 + 0 -5 + -4x = -9 Add '5' to each side of the equation. -5 + 5 + -4x = -9 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = -9 + 5 -4x = -9 + 5 Combine like terms: -9 + 5 = -4 -4x = -4 Divide each side by '-4'. x = 1 Simplifying x = 1
| 4a^2+28a+16=0 | | x+iy=x-iy | | 4a^2-32a+28=0 | | 8(x-5)=2 | | 3+35x=20x-9 | | p+3=3p-5 | | 3x-20=7x+8 | | 3x-20=7x-8 | | 15+7=-3x+25 | | 3y-x=2+2y | | 0.6/x=5/500 | | log(5)(4x+1)=4 | | 14=7+3x | | 12x+3+13x-3=180 | | 3x+26=x+20 | | 3k+4=k-12 | | 52-15y=7 | | ln(4x+7)=1 | | -5x/814y/8 | | -2(x+7)(x-6)=0 | | 1/2*ln2x-lny | | 1/2ln2x-lny | | (1/2ln2x)-lny | | F(x)=3/4cos4x | | -9-5+4+12-x=5 | | Ln(t+4)=3 | | (-4x)+3x= | | ln^2(x+2)-2=0 | | 4y-6-2y-8+y+12= | | 7y-28=42 | | 20a+20b= | | 2sin(x)cos(x)-cos(x)+2sin(x)-1=0 |